THE ROLE OF PEDAGOGICAL TECHNOLOGIES IN PREPARING STUDENTS FOR COMMUNICATION - Karimova Nargiza Mamatkadirovna (Journals Park Publishing, 2023)
In this article, it is mentioned that the dialogue between the teacher and a particular student is important in preparing students for international communication, and the use of special technologies in preparing students for international communication and cooperation is also mentioned.
Keywords: tolerance, interethnic communication, culture, teacher, student, pedagogical technologies.